ANALISIS KESADARAN LINGKUNGAN SISWA UPT SDN 005 BUKIT RANAH - Nazera Izlyn; Rizki Ananda; Yenni Fitra Surya; M. Syahrul Rizal; Iis Aprinawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Environmental awareness is an important part of character education to shape caring behavior towards cleanliness, waste management, and nature preservation. This study aims to describe students' understanding and environmental awareness, the role of teachers, the challenges faced, and the principal's steps in shaping environmental awareness character at UPT SDN 005 Bukit Ranah. This research uses a descriptive qualitative approach, the research subjects include students in grades III, IV, and V, classroom teachers, and school principals. Data were collected through observation, interviews, questionnaires, and documentation, which were then analyzed using the Miles and Huberman model. The results showed that most students have good environmental awareness, such as throwing garbage in its place, caring for plants, and preserving the environment. Teachers play an important role in shaping these habits through exemplary and habituation, although they still face facility and supervision constraints. The principal supports through the Clean Friday program and environmentally friendly canteen. In conclusion, environmental awareness is formed through consistent cooperation between students, teachers and school authorities.